The Middle Path of Sheikh Arsyad al-Banjari: Islamic Moderation in the Heritage of Banjar - Syukri, M.; Amin, Faizal; Sahri (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study examines the concept of Islamic moderation as reflected in the Book of Sabilal Muhtadin, a monumental work of the prominent scholar Sheikh Arsyad that represents the local wisdom of the people of Banjar. This book discusses various aspects of the law of worship and social interaction that are associated with the practice of the life of the Banjar people in the framework of sharia norms. The focus of the study includes a number of local cultural practices, such as the use of tabala (coffins) in funerals, the provision of food for mourners, and the use of latrines (toilets) as a means of defecation and determining the laws on local plants among the Banjar people. These local plant practices and materials are accommodated through a contextual and moderate approach to fiqh, although in some classical fiqh literature it is seen as inappropriate. This research uses a qualitative approach with a literature study method through an analysis of Sheikh Arsyad's thoughts, especially in the Book of Sabilal Muhtadin. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that Sheikh Arsyad was able to formulate fiqh law by considering the social reality of the Banjar community, thus producing a harmonious synthesis between religious values and local traditions.